Validity of the PUSH band 2.0 and Speed4lifts to measure velocity during upper and lower body free-weight resistance exercises - Callaghan, D. E.; Guy, J. H.; Elsworthy, N.; Kean, C. (Journal of Sports Sciences, 2022)
Accuracy and test-retest reliability were assessed for two devices, PUSH Band 2.0 (PUSH) and Speed4lifts. Two identical sessions were performed 6-8 days apart. Twenty rugby league players performed three repetitions with 20%, 40%, 60% and 80% of estimated one repetition maximum for back squat (BS), front squat (FS), and bench press (BP). Velocity was recorded using PUSH, Speed4lifts and 3D motion analysis system (gold standard). Passing-Bablok regression analysis assessed agreement of velocity measures with the gold standard. Intraclass correlation coefficients (ICC) and coefficients of variation (CV) assessed test-retest reliability. PUSH and Speed4lifts were accurate for BS velocities <1.00 m/s and FS velocities <0.65 m/s. PUSH was accurate for BP velocities <0.65 m/s. Speed4lifts was accurate for BP velocities between 0.65-1.00 m/s. PUSH was reliable at all loads (ICC = 0.79-0.92; CV = 2.63-6.89%) except for 20% FS and BP (ICC = 0.49-0.64; CV = 3.13-3.62%). Speed4lifts was reliable at all loads (ICC = 0.70-0.96; CV = 2.57-4.26%) except for 20% BP (ICC = 0.59; CV = 4.59%). These results suggest that both devices are unsuitable for measuring the velocity of BS, FS and BP at faster velocities and at lighter loads.